"But it wasn't like that": The impact of visits to community-based museums on young people's understanding of the commemorated past in a divided society. (2nd October 2021) - McCully, Alan; Weiglhofer, Magdalena; Bates, Jessica
ABSTRACT: This article reports on the impact visits to community-based museums in a divided society, Northern Ireland, had on young people's historical, political, and cultural understanding of the commemorated past. It examines the responses of two student groups, one predominantly Protestant and the other Catholic, to two museums, each presenting its own community's perspective on one contentious aspect of Derry/Londonderry's past. Data were collected through observation, focus groups, and semi-structured interviews from students, teachers, and museum staff. In the emotive environments of the two museums, findings indicated that community background remained important in shaping responses, but critical thinking allied to personal engagement with testimony and artifacts, particularly related to the recent, contentious past, was also influential. In one group, the experience was powerful in causing affective disruption, which challenged established positions, but in the other, it largely consolidated existing norms.